PENGUATAN EFIKASI DIRI MELALUI DOLANAN DRAMA PADA ANAK DENGAN DISABILITAS FISIK - Susanti, I. A.; Prihartini, N. M. L.; Agnesia, K. R.; Dharmayanti, N.M. S.; Hariani, N. W. D. D.; Diastuti, N. N. P.; Utami, P. A. S. (Buletin Udayana Mengabdi; Vol 20 No 4 (2021): Buletin Udayana Mengabdi, 2022)
Children with special needs such as visual disabilities are children who have development and learning barriers. The problem that is often faced is low self-efficacy which affects the ability to interact and socialize with the environment and daily interactions. The purpose of this community dedication is to develop a program to facilitate the interaction between children with visual impairments with non-disabled children through drama games based on symbolic interaction theory to increase self-efficacy. The method for this program is used games or traditional games combined with education in a drama. Children with disabilities from SLB N 1 Denpasar would played games and dramas. The method of implementing the program is divided into seven stages, namely orientation, role and song selection, first-round training, second round training, third round training, performance, and evaluation. The results obtained are guide books and video tutorials for the implementation of activities that can be widely used by the community as a learning method to strengthen the interaction and self-efficacy of children with visual disabilities. Self-efficacy in children with physical disabilities can be trained and developed by strengthening interactions with children with non-disabilities through drama and game.